Pengaturan Kecepatan Motor Arus Searah Variasi Tahanan Jangkar Dan Variasi Tahanan Medan Menggunakan Smart Relay - Sandi Firman Nanda; Firdaus Firdaus; Feranita Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Speed setting plays an important role in the direct current motor, because the motor has a direct current coupling characteristic speed profitable compared to other motors. From both of these characteristics can be used as a basis to set the dc shunt motor speed. If a decline in motor speed due to the increase in load current (Ia), the field current (If) is set (reduced) so that the motor speed be maintained at the desired rotation. In the design of the most important stages of this research. In the design phase to understand the properties, characteristics, specifications of components used and the steps that must be considered by using the block diagram of DC motor supply circuit blocks, smart relay circuit blocks, block string of resistors, and a DC motor circuit blocks, each this circuit has the function block and work differently but interrelated. Based on data and analysis can then be seen that the larger the anchor resistance will decrease the speed of the motor to hold the armature and the greater the speed the greater the resistance to hold field.Keyword : Dc motor speed settings using smart relay